NEOCLASSICAL TRANSPORT AND IOTA SCALING IN THE TJ-‐II STELLARATOR - Castejón, F.; Rubio-Montero, Antonio. J.; López-Fraguas, A.; Ascasíbar, E.; Mayo-García, R. (ANS, 2016)
Neoclassical transport properties are studied in the TJ-II stellarator, taking effective ripple and plateau factor as the figures of merit. Using the DKES code run by grid computing techniques, these two quantities have been estimated as functions of rotational transform and plasma volume. The effective helical ripple increases with plasma volume and rotational transform. These findings suggest the degradation of confinement with iota or volume, which contradicts the scaling laws of energy confinement and the TJ-II experimental results. The plateau factor is almost constant with volume, but it increases following an almost quadratic law with rotational transform. This indicates that the improvement in confinement with iota cannot be explained by neoclassical transport in TJ-II
Keywords: Stellarator scaling; TJ-II stellarator; Neoclassical transport